2001
DOI: 10.1021/jf000615f
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Particle Size Effect on Water Vapor Permeability and Mechanical Properties of Whey Protein/Beeswax Emulsion Films

Abstract: Lipid particle size effects on water vapor permeability (WVP) and mechanical properties of whey protein isolate (WPI)/beeswax (BW) emulsion films were investigated. Emulsion films containing 20 and 60% BW (dry basis) and mean lipid particle sizes ranging from 0.5 to 2.0 microm were prepared. BW particle size effects on WVP and mechanical properties were observed only in films containing 60% BW. WVP of these films decreased as lipid particle size decreased. As drying temperature increased, film WVPs decreased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
126
0
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(151 citation statements)
references
References 13 publications
11
126
0
11
Order By: Relevance
“…Among the macromolecules used in film production, proteins are widely used due to their functional properties and the variety of available sources and low production cost, including caseinates, whey protein, wheat gluten and gelatin [2][3][4][5] . Films based on gelatin have good tensile strength and good gas barrier properties, however, due to its hydrophilic nature, they are not efficient as barrier to water vapor.…”
Section: Introductionmentioning
confidence: 99%
“…Among the macromolecules used in film production, proteins are widely used due to their functional properties and the variety of available sources and low production cost, including caseinates, whey protein, wheat gluten and gelatin [2][3][4][5] . Films based on gelatin have good tensile strength and good gas barrier properties, however, due to its hydrophilic nature, they are not efficient as barrier to water vapor.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, all essential oils except citronella reduced tensile strength and essential oil of thyme reduced stretch percent up to its breaking point. The films containing essential oil of tarragon was not significantly different compared to others, but other essential oils increased the stretch percent (18). Evaluation of the solubility showed that highest and lowest solubility was obtained in control (30.39%) and the treatment containing 0.8 % essential oil (13.6%), respectively.…”
mentioning
confidence: 77%
“…Yongcheng and Park assumed that the average size of the particles in microemulsions usually depends on the type of emulsifier and is predictable [10]. The diameter of particles in emulsion of lipid in the film affects the water permeability of the film and its mechanical properties [11]. Stokes equation includes sedimentation rate (U), diameter of the dispersed phase (d), the density of the dispersing phase (ρP), the density of the dispersed phase (ρL), gravity (g), dynamic viscosity of the dispersion medium (μ) and represents the relationships between the diameter of dispersed particles and the viscosity of the system using Eq 1 [12].…”
Section: Introductionmentioning
confidence: 99%